Current Anti-Integrin Therapy for Ocular Disease. (4th July 2018) - Gonzalez-Salinas, Roberto; Hernández-Zimbrón, Luis F.; Gulias-Cañizo, Rosario; Sánchez-Vela, Mario Alberto; Ochoa-De La Paz, Lenin; Zamora, Ruben; Quiroz-Mercado, Hugo
ABSTRACT: The integrin family of cell adhesion molecules mediates homeostasis, signal transduction, and various other interactions between the cell and the extracellular matrix. Integrins are type-1 transmembrane glycoproteins located on the cell surface, widely expressed in leukocytes, which play an important role in the inflammatory pathway. The purpose of this review is to summarize the current state of anti-integrin therapy and to assess ongoing clinical trials in ocular disease. We performed a search on PubMed, CINAHL, and Embase for the published literature available using the MeSH terms: "integrin therapy" and "αLβ2, " "α4β1" and "α4β7, " "αvβ3, " "αvβ5, " and "αvβ1" and/or "ophthalmology, " and "clinical trials." We used no language restrictions. We generated searches to account for synonyms of these keywords and MESH headings as follows: (1) "integrin, " "therapy, " or "treatment"; (2) "clinical trials, " "ophthalmology, " or "ocular." In addition, the analysis included phase 2 and phase 3 clinical trials with a minimal follow-up of six months. Integrin antagonists have shown their capacity to improve signs and symptoms of patients with dry eye disease, age-related macular degeneration, diabetic macular edema, and vitreomacular traction.